The Gendered Dynamics of the Blue Economy: Women’s Contribution to Sustainable Development in Coastal Communities - Rizky, M. Chaerul; Anwar, Yohny; Ardian, Noni (International Review of Management and Marketing, 2025)
The blue economy, which focuses on the sustainable use of marine resources, has gained increasing attention for its role in promoting economic well- being in coastal communities. Gender equality, as a key factor in the blue economy, is critical for enhancing participation and promoting sustainable development in sectors such as fisheries, marine conservation, and tourism. This study investigates the impact of gender equality and women’s involvement on economic well-being in the context of the blue economy, focusing on coastal communities in Langkat Regency, North Sumatera, Indonesia. A quantitative deductive approach was employed, where a cross-sectional survey was conducted with 375 women respondents, utilizing structured questionnaires to assess three key variables: gender equality, women’s involvement, and economic well-being. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the relationships among these constructs. The results indicate that gender equality positively impacts economic well-being and significantly promotes women’s involvement in sectors such as fisheries, marine conservation, and sustainable tourism. Additionally, women’s involvement mediates the relationship between gender equality and economic well-being, emphasizing the importance of inclusive governance and gender-sensitive policies. These findings highlight the critical role of women in driving sustainable development and economic growth in coastal communities. The study suggests that gender-inclusive policies are essential for achieving both economic and social benefits within the blue economy. Further research is needed to explore strategies for increasing women’s representation in leadership and decision- making roles in this sector.